Effect of a 12-Week Concurrent Training Intervention on Cardiometabolic Health in Obese Men: A Pilot Study - Amaro-Gahete, Francisco J.; Ponce-González, Jesús G.; Corral-Pérez, Juan; Velázquez-Díaz, Daniel; Lavie, Carl J.; Jiménez-Pavón, David (Frontiers in Physiology, 2021)
The present study aimed to investigate the effects of a 12-week concurrent training intervention on cardiometabolic health in obese men. Twelve obese men (42.5 ± 5.3 years old) participated in the current 12−week randomized controlled trial with a parallel group design. The participants were randomly assigned to a concurrent training group or to a no-exercise control group. Anthropometry and body composition assessment were determined by electrical bio-impedance. Blood samples were obtained and a cardiometabolic risk Z-Score was calculated. Energy metabolism-related parameters [i.e., resting metabolic rate (RMR), respiratory quotient (RQ), and substrate oxidation in both resting conditions and during exercise] were determined by indirect calorimetry. Echocardiographic studies were performed using an ultrasound system equipped with a transducer to measure cardiac function. A significant decrease of weight (Δ = −4.21 kg; i.e., primary outcome), body mass index (Δ = −1.32 kg/m2), fat mass (FM; Δ = −3.27 kg), blood pressure (BP; Δ = −10.81 mmHg), and cardiometabolic risk Z-Score (Δ = −0.39) was observed in the exercise group compared with the control group (all P < 0.05), while no significant changes were noted in waist circumference (WC), lean mass (LM), bone mineral content, glycemic and lipid profiles, liver function, nor in energy metabolism-related parameters (all P > 0.1). Moreover, a significant increment of left ventricular (LV) end diastolic diameter (Δ = −4.35 mm) was observed in the exercise group compared with the control group (P = 0.02). A 12-week concurrent training intervention is an effective strategy to induce weight and fat loss with simultaneous reductions of BP and cardiometabolic risk, and improving cardiac function in obese men.